Pakistan Punjab Province : Public Financial Management and Accountability Assessment - World Bank (Islamabad: World Bank, 2013)
This document reports on a Public Financial Management and Accountability Assessment (PFMAA) for the Government of the Punjab. The assessment was conducted with the particular objective of updating the PFMAA published in May 2007 to provide the Punjab Government with an objective, indicator-led assessment of the provincial Public Financial Management (PFM) system in a concise and standardized manner, to form an updated understanding of the overall fiduciary environment of the PFM system and to assist in identifying those areas in need of further reform and development. The assessment was conducted as per the revised PEFA PFM Performance Measurement Framework of 2011 (PEFA Framework). The scope of the current assessment was comprehensive with due consideration of the PEFA Secretariat guidance for repeat assessments. The PFMAA was conducted against 31 PFM performance management indicators (28 for government performance and 3 for donor practices) which are grouped into the critical dimensions of performance of an open and orderly PFM system.